Emotional Intelligence, Social Interaction, and Its Relationship to the Performance of Serving and Receiving Skills in Volleyball Third Stage for Female Students - Ahmed, Zahraa Jawad; Hamoodi, Luma Samer (Journal of Posthumanism, 2025)
The research aims to know the degree of study variables (emotional intelligence - social interaction - serving - receiving the serve) in the research sample, as well as to know the relationship between (emotional intelligence - social interaction) and the performance of the skills (serving - receiving the serve) in volleyball in the research sample. The researchers used the descriptive approach using a correlational approach, as it was appropriate for the research problem and objectives. The research community was represented by third-year female students at the College of Physical Education and Sports Sciences for Woman/University of Baghdad for the academic year (2024-2025), numbering (34) students divided into (2) sections. The research sample represented (100%) of the total research community, as (5) female students, representing (14.705%), were randomly selected by lottery to represent the exploratory sample. The remaining (29) female students represented the main experimental sample, representing (85.294%). There were significant differences between the arithmetic mean and the hypothetical mean for each of (emotional intelligence - social interaction) in favor of the hypothetical mean. This indicates the weakness of the sample in these two variables. The researchers attribute this to the lack of interest in mental and psychological aspects, especially (emotional intelligence - social interaction) among female learners, and the focus primarily on the skill aspect only, despite its significant impact on performance. Conclusion: The low level of emotional intelligence and social interaction among the research sample, and the low level of serving among the research sample members.